Upfront surgery or definitive radiotherapy for p16+ oropharyngeal cancer. A GETTEC multicentric study. Issue 6 (June 2021) - Culié, Dorian; Schiappa, Renaud; Modesto, Anouchka; Viotti, Julien; Chamorey, Emmanuel; Dassonville, Olivier; Poissonnet, Gilles; Bizeau, Alain; Vergez, Sebastien; Dupret-Bories, Agnes; Fakhry, Nicolas; Santini, Laure; et al.
Abstract: Background: The aim of this study was to assess the impact of the initial therapeutic strategy on oncologic outcomes in patients with HPV-positive OPSCC. Methods: All p16-positive OPSCCs treated from 2009 to 2014 in 7 centers were retrospectively included and classified according to the therapeutic strategy: surgical strategy (surgery ± adjuvant radiotherapy and chemotherapy) vs. non-surgical strategy (definitive radiotherapy ± chemotherapy). Univariate, multivariate propensity score matching analyses were performed to compare overall (OS), disease-specific (DSS) and recurrence-free survival (RFS). Results: 382 patients were included (surgical group: 144; non-surgical group: 238). Five-year OS, DSS and RFS were 89.2, 96.8 and 83.9% in the surgical group and 84.2, 87.1 and 70.4% in the non-surgical group, respectively. These differences were statistically significant for DSS and RFS after multivariate analysis, but only for RFS after propensity score matching analysis. Conclusion: In p16+ OPSCC patients, upfront surgery results in higher RFS than definitive radiotherapy ± chemotherapy but does not impact OS.